The Dynamics of Psychological Resilience Study in Last Two Decades - Judijanto, Loso (The Eastasouth Journal of Social Science and Humanities, 2025)
This study employs a bibliometric analysis to explore the evolution of the psychological resilience literature over the past two decades. By systematically examining research articles indexed in Scopus, we identified key themes, authorship patterns, and collaboration networks within the field. Our findings reveal a strong focus on the interconnections between psychological resilience and mental health issues such as depression and anxiety. The analysis highlights the growing importance of cultural factors and the role of global collaboration in shaping research trajectories. The study also notes an increase in interdisciplinary approaches and methodological innovations, enhancing our understanding of resilience across various populations. This bibliometric mapping provides valuable insights into the dynamic nature of resilience research and underscores the expanding scope of this vital psychological construct in addressing global mental health challenges.